What is sexual harassment? : from Capitol Hill to the Sorbonne - Saguy, Abigail Cope, 1970- (University of California Press, 2003)
In France, a common notion is that the shared interests of graduate students and their professors could lead to intimate sexual relations, and that regulations curtailing those relationships would be both futile and counterproductive. By contrast, many universities and corporations in the United States prohibit sexual relationships across hierarchical lines and sometimes among coworkers, arguing that these liaisons should have no place in the workplace.